Regulation of the PKCθ-NF-κB Axis in T Lymphocytes by the Tumor Necrosis Factor Receptor Family Member OX40 - So, Takanori; Croft, Michael (Frontiers in Immunology, 2012)
Antigen primed T lymphocytes need to expand and persist to promote adaptive immunity. The growth and survival signals that control this are in large part provided by the NF-κB pathway in activated or effector/memory T cells. Although several membrane receptors impact NF-κB activation, signaling from OX40 (CD134, TNFRSF4), a member of the tumor necrosis factor receptor (TNFR) superfamily, has proven to be important for T cell immunity and a strong contributor to NF-κB activity. PKCθ directs the TCR and CD28-dependent assembly of a CBM complex (CARMA1, BCL10, and MALT1) for efficient activation of NF-κB, raising the question of whether other membrane bound receptors that activate NF-κB also require this PKCθ-CBM axis to control TCR-independent T cell activity. We discuss here our recent data demonstrating that after ligation by OX40L (CD252, TNFSF4) expressed on antigen-presenting cells, OX40 translocates into detergent-insoluble membrane lipid microdomains (DIM or lipid rafts) in T cells irrespective of TCR signals, and assembles into a novel signaling complex containing PKCθ, together with TRAF2, RIP1, the CBM complex, and the IKKα/β/γ complex. PKCθ is required for optimal NF-κB activation mediated by OX40 and thus works as an essential component of this OX40 signalosome. We also discuss the likelihood that other TNFR superfamily molecules might complex with PKCθ in T cells, and whether PKC isoforms may be critical to the function of TNFR molecules in general.